Traditional Knowledge of Wild Medicinal Plants of Baria Forest Division, Dahod District, Gujarat State - Yadaiah, G.; Oshi, Parul J.; Oza, Bindiya (Indian Forester, 2011)
Survey was conducted in randomly selected 23 villages of the Baria forest division. A systematic questionnaire was prepared and based on it questions were asked to the tribals. From the survey, 94 species were identified which are being used as folk medicine by the tribal people of Baria division. Some of these plants were commonly used in all the villages surveyed for same diseases, but there are some plants which are varied in their uses among villages. Most of the plants which are used as folk medicines by tribals of the Baria division are collected from the adjoining forest areas while some species are also found in the adjoining areas of the farm and households of tribals. The medicinal plants commonly used by tribal are Butea monosperma, Plumbago zylenica, Tridax procumbens, Leptadenia reticulata, Helicteres isora, Cissus quadrangularis etc.